Harold Garfinkel and the Postphenomenology of Social Action (II) - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 2011)
This article is written in honour of Harold Garfinkel (October 29, 1923–April 21, 2011), a thinker who has been greatly influential, directly and indirectly, in shaping many fields of academic study. The aim is to explicate the question ‘What is Ethnomethodology?’ by making explicit the early (1967) and late (2002) versions of Garfinkel’s ethnomethodology. This is done in two parts: the first looks at Garfinkel’s attempts to articulate and operationalise different sociological conceptions of social action; the second turns to Harold Garfinkel and Anne Rawls’s re-specification of Durkheim. The article argues that this ‘radical new beginning’ represents an opportunity for sociologists to focus on the unexamined relations between the various postphenomenological conceptions of social action, the critical tradition of social theory, and the ‘visible, however unnoticed’ core of ethnomethodological ‘theory’.